인진호탕 투여로 발생한 완고한 소양감의 호전 및 피부 색소 발현에 대한 증례보고 - 이찬; 서형범; 조임학; 허기윤; 강희경; 한창우; 김소연; 최준용; 박성하; 윤영주; 홍진우; 권정남; et al. (대한한방내과학회지, 2020)
Objectives: This study reports a case of a 66-year-old Korean female with stubborn pruritus and assesses the effectiveness of Korean medical treatment. Methods: A patient was treated with acupuncture, electro-acupuncture, and herbal medicine. We evaluated the improvement in symptoms by changes in global assessment (G/A) and sleep quality. Results: After Korean medical treatment, improvements were observed in G/A, and sleep quality. Skin and excretions turned blue to green, with no abnormal findings on the examination. Conclusions: This study suggests that Korean medical treatment is effective in treating stubborn pruritus caused by prurigo. Further studies are needed.